Analisis Pemahaman Mahasiswa Mengenai Fitur Dan Manfaat QRIS Di Lingkungan Akademik - Siregar, Zainal Arifin; Utari, Ulfa (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2024)
This study aims to measure students' understanding of using QRIS (Quick Response Code Indonesian Standard) as a non-cash payment method. The study focuses on students' knowledge of QRIS definitions and mechanisms, features such as MPM, CPM, and QRIS Cross Border, and its benefits in terms of time efficiency, security, and transaction convenience. The research employed a descriptive quantitative method with 50 student respondents from the Faculty of Business and Humanities, Universitas Tjut Nyak Dhien. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics. The results indicate that most students have a good understanding of QRIS, especially regarding its benefits and usage experience, with 80% of respondents agreeing or strongly agreeing. However, technical understanding of QRIS features varied, with 20% of respondents remaining neutral. The study concludes that the QRIS socialization program is effective in enhancing students' understanding but requires more in-depth education on technical aspects. This research contributes to identifying the needs for digital financial literacy among the younger generation.